MEMBANGUN EKONOMI LOKAL MELALUI AKSI BERSIH-BERSIH PANTAI DAN TRANSPLANTASI TERUMBU KARANG DI DESA WISATA KUTA LOMBOK - Satya Praditha, Regza; Sahruni, Maulida; Laily Tri Azaria, Nur; Pracoyo, Atas; Akbar, Ajrial; Hasna Maulani, Septia; Awwali Alwan, Idiatil; Sasmita, Rohana; Ivan Naufal, M.; Hapizatin Napis, Nurul; Agung Wahyunanda Umar, Gigih (Universitas Mataram, 2025)
Kuta Lombok, a tourism village located on the southern coast of Lombok Island, West Nusa Tenggara, has become a favorite destination for both domestic and international tourists due to its stunning natural beauty. However, this beauty is challenged by environmental issues such as waste pollution and damage to marine ecosystems. This article discusses efforts to build the local economy through beach clean-up actions and coral reef restoration in Kuta Tourism Village. The activities included surveys, observations, promotion, practice, and documentation. Beach clean-up and coral transplantation are part of environmental conservation efforts involving local partners, the local community, and school children. The beach clean-up focused on waste collection, while coral transplantation used web spider -type coral frames to facilitate coral growth. This community service activity is expected to have a sustainable positive impact on the environment and the local community.